Penyuluhan Tentang Keselamatan dan Kesehatan Kerja di Bidang Kelistrikan pada Masyarakat Desa Muara Badak - Wafi, Mochammad Fachri Hibatul; Taqiyuddin, Taqiyuddin; Setianingsih, Diah Patriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Electricity is a vital enabler for community life in all aspects, making it an ever-present factor in daily activities. This holds true for Muara Badak Village, where the majority of residents work in mining, plantations, and aquaculture. Evidence of this can be seen in the widespread installation of solar panels in community plantation areas, on fish ponds (tambak), and the use of independent generators in homes. However, this widespread installation of electrical equipment isn't always accompanied by an understanding of electrical hazards. This outreach program aims to educate the people of Muara Badak Village on the proper handling of electrical equipment. By doing so, it can reduce the risk of accidents related to electrical work, such as electrocution, fires, and even fatalities. The program also covers the appropriate response to electrical accidents, ensuring the community can manage such situations safely and effectively.